2022
DOI: 10.1136/jim-2021-002285
|View full text |Cite
|
Sign up to set email alerts
|

A model established using marital status and other factors from the Surveillance, Epidemiology, and End Results database for early stage gastric cancer

Abstract: Currently, the postoperative prognosis of early stage gastric cancer (GC) is difficult to accurately predict. In particular, social factors are not frequently used in the prognostic assessment of early stage GC. Therefore, this study aimed to combine the clinical indicators and social factors to establish a predictive model for early stage GC based on a new scoring system. A total of 3647 patients with early stage GC from the Surveillance, Epidemiology, and End Results database were included in this study. A K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Marital status is an interesting predictor of cancer outcomes. A 2022 study demonstrates that married patients have superior survival after GC diagnosis, compared to those who are single or separated, suggesting that social support provides beneficial outcomes regarding early detection, treatment and survival [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Marital status is an interesting predictor of cancer outcomes. A 2022 study demonstrates that married patients have superior survival after GC diagnosis, compared to those who are single or separated, suggesting that social support provides beneficial outcomes regarding early detection, treatment and survival [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the international tumor-node-metastasis (TNM) staging system only relies on anatomical and pathological features for disease assessment, without considering many other important relevant factors, such as age, sex, and other demographic characteristics [86,87]. Numerous studies have shown that the clinical stage alone is not sufficient to predict the prognosis of patients with cancer [87][88][89][90]; therefore, further analysis of demographic characteristics is necessary [36].…”
Section: Demographic Characteristicsmentioning
confidence: 99%